Exploring Speech Act Patterns in Lecturer–Student Online Interactions - Nurfadilah; Muh. Hasbi; Aslan Abidin (Journal of Educational Management Research, 2026)
This study aims to investigate the types of illocutionary speech acts most frequently produced by lecturers and students during online classroom interactions. Focusing on the illocutionary dimension, the study explores how language is used to convey intentions, requests, and social interactions in educational settings. A descriptive qualitative approach was employed, analyzing interactions based on Searle and Yule’s speech act theories. Data were collected from recorded online class sessions, transcribed, and systematically coded to identify patterns of speech acts. The findings indicate that directive acts are the most dominant, reflecting attempts by speakers to elicit actions from others. Assertive acts, which demonstrate the speaker’s authority and provide information, were the second most frequent. Expressive acts, conveying emotions, attitudes, or respect, appeared less frequently, while commissive acts, related to commitments to future actions, were the least observed. These results highlight the central role of directive and assertive speech in managing online classroom interactions and facilitating effective communication. The study suggests that awareness of speech act patterns can enhance teaching strategies, improve student engagement, and reduce miscommunication in online learning environments.